COMPETENCY-BASED TRAINING IN NURSING: LIMITS AND POSSIBILITIES - Silvia Franco da Rocha Tonhom; Maria Cristina Guimarães da Costa; Cássia Galli Hamamoto; Anete Maria Francisco; Haydée Maria Moreira; Romeu Gomes (SciELO, 2014)
Objective To analyze the possibilities and limits of competency-based training in nursing. Method An integrative review of the literature on the subject was carried out, and an analysis was made of the results of a survey evaluating a nursing course based on areas of competency. A dialog was then established between the review and the results of the research. Results On the question of which theoretical type of competency the articles from the literature relate to, there is a predominance of the constructivist perspective, followed by the functionalist approach and the dialog-based approach. In the dialog between the literature and the research, limits and possibilities were observed in the development of a training by areas of competency. Conclusion The dialog-based approach to competency is the proposition that most approximates to the profile defined by the National Curriculum Guidelines for training in nursing, and this was also identified in the evaluation survey that was studied. However, it is found that there are aspects on better work is needed, such as: partnership between school and the workplace, the role of the teacher, the role of the student, and the process of evaluation.